The Development of Android-Based Multistage Fitness Test Software to Measuring Vo2 Max - Swandri, Oka Veliana (Universitas Negeri Semarang (Unnes), 2018)
This study aims to produce an on-field test software, android-based multistage fitness test, that is valid and reliable, to determine the feasibility level of android-based multistage fitness test software based on experts’ judgments; also to determine the effectiveness level of android-based multistage fitness test software. This research is a development by following Borg & Gall design. Validity test using t paired sample t-test. Results of the study: 1) a product of android-based multistage fitness test software that serves to guide the course of the multistage fitness test in Indonesian with automatic recording of results, 2) a tester is able to supervise 7 test participants in a single test, 3) the results of the assessment of media experts, material experts and practitioners, the product is considered feasible with the average percentage of 70% (Good), 4) The effectiveness test results show that the correlation value is 0.995 and the sig value. (2-tailed) of 0.145 (p> 0.05). It can be concluded that there is no difference between the results of Android-based Multistage Fitness Test Software with the results of manual Multistage Fitness Test. Android-based Multistage Fitness Test Software to measure VO2 Max is feasible to use.